Cancer stem cells, tumor dormancy, and metastasis - Patel, Purvi; Chen, Emily (Frontiers in Endocrinology, 2012)
Tumor cells can persist undetectably for an extended period of time in primary tumors and in disseminated cancer cells. Very little is known about why and how these tumors persist for extended periods of time and then evolve to malignancy. The discovery of cancer stem cells (CSCs) in human tumors challenges our current understanding of tumor recurrence, drug resistance, and metastasis, and opens up new research directions on how cancer cells are capable of switching from dormancy to malignancy. Although overlapping molecules and pathways have been reported to regulate the stem-like phenotype of CSCs and metastasis, accumulated evidence has suggested additional clonal diversity within the stem-like cancer cell subpopulation. This review will describe the current hypothesis linking CSCs and metastasis and summarize mechanisms important for metastatic CSCs to re-initiate tumors in the secondary sites. A better understanding of CSCs’ contribution to clinical tumor dormancy and metastasis will provide new therapeutic revenues to eradicate metastatic tumors and significantly reduce the mortality of cancer patients.